The Regional Economic Effects of Military Base Realignments and Closures in Germany - Alfredo R. Paloyo; Colin Vance; Matthias Vorell (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Within the context of the current political discussion over base realignments and closures (BRACs) in Germany, this study provides policy guidance by examining the economic consequences to the surrounding community. We identify the causal effect of a reduction in military personnel on a number of socioeconomic indicators within the peripheries of military bases. The BRACs within the German armed forces is used an exogenous source of variation that allows for the estimation of the causal effect of a particular demand shock on household income, output, unemployment, and tax revenue within a specified buff er zone around each base. The analysis covers 298 communities for the period 2003-2007. Consistent with evidence found elsewhere, we find that these base adjustments have only a marginal impact on the local community in which the bases are located. – – In der aktuellen politischen Debatte über Standortschließungen und -verlagerungen der Bundeswehr gibt diese Studie Politikempfehlungen auf Grundlage einer Untersuchung der ökonomischen Effekte entsprechender Standortveränderungen. Identifiziert wird der kausale Effekt des Abbaus von Militärpersonal auf eine Reihe sozioökonomischer Indikatoren innerhalb eines festgelegten Umkreises um betroffene Stützpunkte. Variation zwischen den Standorten und der Prozess der Schließung oder Verlagerung werden als Quelle exogener Variation verwendet. Mithilfe dieser Variation wird der Effekt des spezifischen Nachfrageschocks auf Haushaltseinkommen, BIP, Arbeitslosigkeit und Steuereinnahmen innerhalb eines festgelegten Radius um den betroffenen Stützpunkt untersucht. Die Analyse umfasst 298 Gemeinden und den Zeitraum 2003 bis 2007. Im Einklang mit vorhandener Evidenz für andere Länder lässt sich feststellen, dass Standortschließungen und -verlagerungen nur marginale Auswirkungen auf die betroffenen Gemeinden haben.
Keywords: H56; K42; R19; 330; Geographic information system; armed forces; regional adjustment; Militärstandort; Regionale Inzidenz; Wirtschaftliche Anpassung; Deutschland